Black-white asymmetry in visual perception - Zhong‐Lin Lu; George Sperling (2012)
Abstract With eleven different types of stimuli that exercise a wide gamut of spatial and temporal visual processes, negative perturbations from mean luminance are found to be typically 25% more effective visually than positive perturbations of the same magnitude (range 8–67%). In Experiment 12, the magnitude of the black–white asymmetry is shown to be a saturating function of stimulus contrast. Experiment 13 shows black–white asymmetry primarily involves a nonlinearity in the visual representation of decrements. Black–white asymmetry in early visual processing produces even-harmonic distortion frequencies in all ordinary stimuli and in illusions such as the perceived asymmetry of optically perfect sine wave gratings. In stimuli intended to stimulate exclusively second-order processing in which motion or shape are defined not by luminance differences but by differences in texture contrast, the black–white asymmetry typically generates artifactual luminance (first-order) motion and shape components. Because black–white asymmetry pervades psychophysical and neurophysiological procedures that utilize spatial or temporal variations of luminance, it frequently needs to be considered in the design and evaluation of experiments that involve visual stimuli. Simple procedures to compensate for black–white asymmetry are proposed.